Realitas Sosial Kelas Marginal Kajian Marxis terhadap Cerpen “Bansos” dan “Bulan yang Jatuh di Atap Rumbia” - Shofia Permata Sari; Yasinta Anggi Aulia; Maheswari Tahara Surya Ningrum Basmutia (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
Poverty and social inequality remain persistent realities in modern society, particularly affecting marginalized groups who are often excluded by unfair economic and political systems. This study aims to analyze the representation of marginalized social classes in the short stories “Social assistance” by Satmoko Budi Santoso and “The Moon That Fell on a Rumbia Roof” by A. Warits Rovi through a sociological approach to literature using Marxist theory. The research employs a descriptive qualitative method, with primary data derived from the narratives of both short stories and supported by secondary data from theoretical and relevant literary studies. The results show that “Social assistance” portrays the marginalization of Karmin through discrimination in the distribution of social assistance caused by an unjust bureaucratic system, while “The Moon That Fell on a Rumbia Roof” highlights the suffering of Salma, a single mother who experiences labor exploitation and political discrimination. Both stories reveal the inequalities experienced by marginalized classes in economic, social, and political aspects, as well as their diverse responses ranging from submission to symbolic resistance. These works reflect real social disparities and serve as critiques of systems that maintain the dominance of the ruling class. Thus, literature plays an essential role as a reflective medium capable of raising social awareness about issues of injustice. The contribution of this research lies in its effort to enrich sociological studies of literature in Indonesia by examining the representation of marginalized classes and forms of social resistance in contemporary literary works. Future research is suggested to expand the scope to other literary texts with different social and cultural contexts and to combine Marxist theory with interdisciplinary approaches such as feminism or postcolonialism to provide a more comprehensive understanding of social inequality in literature